Papua New Guinea: A Potential Refuge for Threatened Indo–Pacific River Sharks and Sawfishes - Grant, Michael I.; White, William T.; Amepou, Yolarnie; Appleyard, Sharon A.; Baje, Leontine; Devloo-Delva, Floriaan; Feutry, Pierre; Ibana, Dotty; Jogo, Dick J.; Jogo, Stanley; Kyne, Peter M.; Mana, Ralph; et al. (Frontiers in Conservation Science, 2021)
The conservation of threatened elasmobranchs in tropical regions is challenging due to high local reliance on aquatic and marine resources. Due primarily to fishing pressure, river sharks (Glyphis) and sawfishes (Pristidae) have experienced large population declines in the Indo-Pacific. Papua New Guinea (PNG) may offer a refuge for these species, as human population density is low, and river shark and sawfish populations are thought to persist. However, few data are available on these species in PNG, and risk posed by small-scale fishers is poorly understood. This study observed elasmobranch catches in small-scale fisheries in riverine and coastal environments in the East Sepik (northern region), Gulf, and Western Provinces (southern region) of PNG. Surveys were conducted over a period of weeks to months in each region, during the dry season across seven field trips from 2017 to 2020. We observed a total of 783 elasmobranchs encompassing 38 species from 10 families. River sharks made up 29.4% of observations in the southern region, while sawfishes made up 14.8 and 20.3% in the northern and southern regions, respectively. River sharks were commonly caught by small-scale fishers in lower riverine environments in southern PNG, while sawfishes were generally less common and mainly observed through dried rostra. The primary threat to river shark and sawfish populations is their capture by small-scale fishers targeting teleosts for swim bladder. Persisting populations of river sharks and sawfishes indicate that PNG is the second known nation with viable populations of multiple species in the Indo-Pacific. However, populations are declining or at high risk of decline, and fisheries management and conservation are required to realize the potential of PNG as a long-term refuge.